The Egyptian uprising : waning threat of the jihadists - Mohamed Redzuan Salleh (2012)
The Egyptian uprising is showing no sign of abating. Amidst the Western paranoia that Islamists will rise to power, is the prospect of this uprising turning into a jihadist threat real or imagined?